The Effect of Skipping Training on Straight Kick Speed in Pencak Silat at State Senior High School 1 Katapang - Nurjanah Jayanti; Agus Rusdiana; Iman Imanudin (Universitas Negeri Semarang, 2025)
This study aims to determine the effect of skipping training on straight kick speed in pencak silat. The method used is a quasi-experimental with a pretest-posttest control group design. The research subjects consisted of 10 extracurricular pencak silat athletes at Senior High School 1 Katapang who were divided into two groups, namely the experimental group and the control group. The experimental group was given treatment in the form of skipping training for 3 weeks with a frequency of 4 times a week. The instrument used was a straight kick speed test in 10 seconds. The results of the paired sample t-test showed that there was a significant increase in the experimental group (p < 0.05), with an average increase of 6.2 kicks. While in the control group, no significant increase was found. The independent sample t-test also showed a significant difference between the experimental and control groups (p < 0.05). Thus, skipping training is proven to be effective in increasing straight kick speed in pencak silat athletes. The results of this study can be used as a reference by coaches in developing training programs aimed at improving athlete performance.